Potencialidades do uso do moodle na gestão educacional de bolsas Capes do sistema Universidade Aberta do Brasil no âmbito da Universidade Federal de Santa Maria - Castro, João Juliano Monteblanco (2019)
This dissertation analyzes the potential of using the Virtual Learning Environment (AVEA) Moodle, as a tool to support educational management in the scholarship sector of the Open University of Brazil (UAB), within the Federal University of Santa Maria (UFSM), and managed by the Center for Educational Technology (NTE). The NTE uses as educational network technologies as tools to support educational management and training. Taking into account a growing integration of technologies that converge to the optimization of work routines, the use of AVEA Moodle is a innovative and technological tool to support educational management, training and democratization of information. Thus, this project has as general objective to evaluate the potentialities of AVEA Moodle as a support to the Coordination of Improvement of Higher Education Personnel (CAPES) referring to the courses of the UAB system, managed by the NTE in UFSM. The specific objectives of this project are: instrumentalize the course coordinators, mentoring coordinators and the NTE administrative sector in the use of AVEA Moodle for educational management of authorization of the CAPES scholarship of the UAB system at UFSM; elaborate a tutorial with information on the processes used in the educational management of the CAPES scholarships of the UAB system in UFSM (product); and to hold an event to evaluate the instrumentation of the educational management of authorization of the CAPES scholarships of the UAB system in UFSM and the tutorial.The bibliographic review first deals with a study of theories about UAB, such as the UAB system, CAPES, the Management System for Scholarships (SGB), the context of the CAPES scholarships of the UAB system and the scholarship sector of NTE. Therefore, it is approached the Virtual Environment of Teaching-Learning, having as subitems the AVEA Moodle and the descriptive of the possibilities of use of Moodle. Finally, the presentation of "tutorial" and "training". The results demonstrated that the use of the educational technologies in the network, in this case the potential use of the AVEA Moodle as support to the educational management in the mediation of CAPES scholarships of the UAB System make the process more fluid, democratic and transparent, being a differential in the instrumentalization and democratization of information.